PERANAN AUDIT OPERASIONAL DALAM MENUNJANG EFEKTIVITAS PENJUALAN PADA PT. CEN TUNG INTERNATIONAL Sidoarjo - Alfian Helmy (Fakultas Ekonomi, 2018)
Operational audit is an appropriate tool for management to assess the level of effectiveness of the company's operations, especially in sales activities. Because the sale is a means used by the company to obtain the maximum profit possible. This study aims to determine the level of sales effectiveness and to determine the role of Operational Audit at PT. CEN TUNG INTERNATIONAL Sidoarjo. This research is done by using quantitative descriptive method. The results show that the effectiveness of sales in terms of budget and sales realization is able to meet the targets set by the company. For operational audit that has done have a role in supporting the effectiveness of sales at PT. CEN TUNG INTERNATIONAL Sidoarjo. The conclusion of the results of this study is that sales in 2014, 2015 and 2016 have been implemented effectively by PT. CEN TUNG INTERNATIONAL Sidoarjo, this can be seen from the results of the percentage of budget reports and the realization of sales for three years ie the period 2014-2016.